The Concept Of Community-Based Tourism Development In Situ Tandon Ciater - Tryasnandi, Agung; Maryani, Enok; Andari, Rini (Journal of Tourism Sustainability, 2023)
Sustainable development must embrace the three basic principles of ecological sustainability, social and cultural sustainability, and economic sustainability for both present and future generations. The community must participate in the implementation of tourism in their area, because this involves economic, social and cultural issues of the community as well as the conservation of the nature in which they live. One of the concepts of sustainable tourism development that is oriented towards community empowerment is Community Based Tourism (CBT) which is a critical idea from conventional tourism development which often ignores rights and does not involve the community in the process. The research method used is descriptive qualitative with data collection techniques through the stages of observation, interviews and focus group discussions and documentation. Research activities consist of preliminary studies, conceptual modeling, validation and revision, and model testing. Data analysis uses an interactive analytical model from Miles and Huberman which allows data analysis when researchers are in the field or after returning from the field. This research resulted in a development concept based on community empowerment through three stages of development: (1) tourism destination development program, (2) tourism marketing development program, (3) partnership development program.